Lemon Balm Extracts Prevent Breast Cancer Progression In Vitro and In Ovo on Chorioallantoic Membrane Assay. (14th April 2020) - Ghiulai, Roxana; Avram, Stefana; Stoian, Dana; Pavel, Ioana Zinuca; Coricovac, Dorina; Oprean, Camelia; Vlase, Laurian; Farcas, Claudia; Mioc, Marius; Minda, Daliana; Motoc, Andrei; Szuhanek, Camelia; et al.
Abstract : Breast cancer is the most frequently diagnosed malignant pathology, representing the primary cause of cancer death in women. Natural products are an appealing strategy to limit the progression of the disease. Targeting angiogenesis in breast cancer may positively impact on poor prognosis of breast cancer. As source of natural compounds, we investigated the leaves of Melissa officinalis L. (MO), known as lemon balm, an aromatic plant that spontaneously grows in the South and Western areas of Romania, being traditionally recommended as anxiolytic, antispasmodic, or as digestive remedy. Our aim was to investigate the phytochemical profiling and the antiangiogenic and chemopreventive bioactivity of MO from Banat region, on breast cancer. Two ethanolic extracts of MO (MOE96 and MOE70) and one methanolic extract (MOM80) were subjected to polyphenol and triterpene profiling by HPLC-MS, and the antioxidant capacity was evaluated. The antiangiogenic potential was investigated using the chorioallantoic membrane assay (CAM). The MTT(3-(4, 5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide) assay was used to investigate the cytotoxic effects on MCF-7 and MDA-MB-231breast cancer cells, as well as on MCF-10A normal breast epithelial cells, while apoptosis was performed by DAPI staining. Rosmarinic acid (RA) and ursolic acid (UA) were revealed as dominant phytocompounds. The highest concentration in phytochemicals were found in MOM80; MOE96 was more concentrated in UA, while MOE70 extracted more RA. MOE96 inhibited cancer progression and angiogenesis in the in ovo CAM model using MDA-MB-231 cells, inhibiting breast cancer progression and angiogenesis for the MDA-MB-231 breast cancer cell line; no secondary tumoral areas were registered, indicative for a preventive effect against breast tumor cell invasiveness. The highest cell inhibitory activity was also exhibited by MOE96, in particular against the estrogen receptor positive MCF7 breast cancer cell line, with no cytotoxic effect on healthy cells. The estrogen receptor positive MCF7 cell line proved to be more sensitive to the extract antiproliferative activity than the triple negative MDA-MB-231 breast cancer cell line. Nevertheless, the chemopreventive potential of MOE96 extract is phenotype-dependent and is rather related to the apoptosis and antiangiogenic effects suggesting a multitargeted mechanism of action due to its multiple compound composition next to a concentration ratio of RA : UA in favor of UA.